2020
DOI: 10.3389/fneur.2020.00376
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 10 and Heart Fatty Acid-Binding Protein as Early Outcome Predictors in Patients With Traumatic Brain Injury

Abstract: Background: Patients with traumatic brain injury (TBI) exhibit a variable and unpredictable outcome. The proteins interleukin 10 (IL-10) and heart fatty acid-binding protein (H-FABP) have shown predictive values for the presence of intracranial lesions. Aim: To evaluate the individual and combined outcome prediction ability of IL-10 and H-FABP, and to compare them to the more studied proteins S100β, glial fibrillary acidic protein (GFAP), and neurofilament light (NF-L), both with and without clinical predictor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…In line with this finding, it has been previously reported that most of the clinical studies have not identified a correlation between blood IL-10 levels and GCS scores (33). These results suggest that the best diagnostic value in discriminating patient outcomes after TBI is achieved by utilizing biomarkers in combination, which echoes our other recent findings in the acute diagnostics of TBI (19) and outcome prediction (34). A possible explanation for the higher HCTS threshold in the panel analysis is that biomarkers provide additional accuracy to the predictive power of the HCTS permitting patients with a favorable outcome to have some traumatic intracranial findings.…”
Section: Aβ42supporting
confidence: 89%
See 1 more Smart Citation
“…In line with this finding, it has been previously reported that most of the clinical studies have not identified a correlation between blood IL-10 levels and GCS scores (33). These results suggest that the best diagnostic value in discriminating patient outcomes after TBI is achieved by utilizing biomarkers in combination, which echoes our other recent findings in the acute diagnostics of TBI (19) and outcome prediction (34). A possible explanation for the higher HCTS threshold in the panel analysis is that biomarkers provide additional accuracy to the predictive power of the HCTS permitting patients with a favorable outcome to have some traumatic intracranial findings.…”
Section: Aβ42supporting
confidence: 89%
“…The outcome prediction ability of IL-10 after TBI has been controversial, although it has shown some potential in predicting mortality (33). However, a recent study utilizing partially same cohort as in this study demonstrated that both IL-10 and H-FABP improved outcome prediction abilities of panels consisting of more studied biomarkers and clinical covariates in both mild TBI and TBIs of all severities (34).…”
Section: Aβ42mentioning
confidence: 65%
“…Similarly, reduced IL-10 serum levels were associated with a more unfavorable prognosis in patients with acute coronary syndromes [31]. IL-10 was an early outcome predictor in traumatic brain injury patients [32]. The differences in these studies might be caused by differences in the number of patients, time of onset of the disease, population, testing methods, and reagents.…”
Section: Discussionmentioning
confidence: 99%
“…The number of biomarkers necessary to achieve sufficient diagnostic specicity is an assumption based on recent and ongoing clinical studies. 21,[98][99][100] the traditional GOx labelling, enabling low-cost detection of NSE biomarker with the detection limit of 8.9 pg mL À1 (cutoff for mTBI 20 ng mL À1 ) 59 and within the dynamic linear range of 0.01-100 ng mL À1 . However, in addition to the multi-step reagent-demanding nature of the proposed sandwich assay, the storage stability is reported to be relatively short owing to the usage of easy-broken liposomes.…”
Section: Potentiometric (Bio)sensorsmentioning
confidence: 99%
“…The search for the 'ideal' mTBI biomarkers still faces many challenges, such as insufficient specicity, as well as inuence of age, gender, injury severity, pre-existing medical conditions and other individual differences. 12,20,21 TBI biomarker discovery today is mainly focused on detection at very early stages aer injury (hyper acute and acute TBI), which will allow for implementation of patient treatments at an earlier time point. For the chronic stages of mTBI, Tau protein and phosphorylated-Tau are under examination as markers of neurodegeneration for in vivo detection of neurodegenerative disorders which are possible long-term sequelae of mTBI such as Alzheimer's disease (AD) and chronic traumatic encephalopathy (CTE).…”
Section: Introductionmentioning
confidence: 99%